J/[psi] production in proton-nucleus collisions at 158 and 400 GeV - Arnaldi, Roberta; Banicz, Karoly; Damjanović, Sanja; Specht, Hans Joachim (Physics letters, 2012)
The NA60 experiment has studied J/ψ production in p-A collisions at 158 and 400 GeV, at the CERN SPS. Nuclear effects on the J/ψ yield have been estimated from the A-dependence of the production cross section ratios σJ/ψA/σJ/ψBe (A=Al, Cu, In, W, Pb, U). We observe a significant nuclear suppression of the J/ψ yield per nucleon-nucleon collision, with a larger effect at lower incident energy, and we compare this result with previous observations by other fixed-target experiments. An attempt to disentangle the different contributions to the observed suppression has been carried out by studying the dependence of nuclear effects on x2, the fraction of the nucleon momentum carried by the interacting parton in the target nucleus.